Design and Manufacture of Dynamic Assemblies and Compo-Site Drive Shafts for Tiltrotor - Barlet-Bas, S.; Malburet, F.; Roucoules, L.; Lopez, C.; Pierrel, B.; Orsoni, F.; Valembois, G. (My University, 2023)
The submitted paper aims to present the development of the components of a mechanical drive line using composite shafts between an engine and a rotor. This project is part of the STEADIEST (Supercritical Composite main Drive SysTem) project funded by H2020 Clean-Sky 2, July 2019 to November 2022. Project team was made up of Nexteam group, Conseil & Technique (compagnies in the aircraft industry - France) and Arts et Métiers (University - France). There were two objectives during this work. The first one was to identify and implement a global design method able to return optimized product by taking into consideration costs induced by design choices. The second objective was to develop and demonstrate the validity of our design process through STEADIEST case study. A design method has been proposed and demonstrate a good performance in solution space design exploration, leading on best technical choices based on current information. Finally, STEADIEST case study has been validated through critical frequency analysis and experiments.
Keywords: Aircraft Design